2006
DOI: 10.1038/modpathol.3800661
|View full text |Cite
|
Sign up to set email alerts
|

The receptor for advanced glycation end products and its ligands: a new inflammatory pathway in lung disease?

Abstract: The binding of the receptor for advanced glycation end products (RAGE) with its ligands begins a sustained period of cellular activation and inflammatory signal amplification in different tissues and diseases. This binding could represent an as yet uninvestigated pathway of inflammatory reaction in the lung, where the presence of the receptor has been largely documented and advanced glycation end products (AGEs) are produced by nonenzymatic glycation and oxidation of proteins and lipids, driven by smoke and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
108
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 30 publications
10
108
2
1
Order By: Relevance
“…In other systems, S100A12 is known to be expressed in granulocytes but not in monocytes or resident macrophages (Vogl et al 1999a;Pietzsch and Hoppmann, 2009). S100A12 expression in granuloma macrophages, including epithelioid cells and MGC specifically, has been reported, in human systems, in the last few years (Kim et al 2006;Morbini et al 2006;Campo et al 2007); the expression of S100A9 and S100A8 was not analysed in these works. Other works have reported widely different observations on the expression of S100A9 and S100A8 in these cell types; these observations include co-expression of both, expression of only S100A9, and lack of expression of either (Zwadlo et al 1988;Delabie et al 1990;Aguiar-Passeti et al 1997;Arai et al 1999;Sunderkotter et al 2004;Kurata et al 2005;Terasaki et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…In other systems, S100A12 is known to be expressed in granulocytes but not in monocytes or resident macrophages (Vogl et al 1999a;Pietzsch and Hoppmann, 2009). S100A12 expression in granuloma macrophages, including epithelioid cells and MGC specifically, has been reported, in human systems, in the last few years (Kim et al 2006;Morbini et al 2006;Campo et al 2007); the expression of S100A9 and S100A8 was not analysed in these works. Other works have reported widely different observations on the expression of S100A9 and S100A8 in these cell types; these observations include co-expression of both, expression of only S100A9, and lack of expression of either (Zwadlo et al 1988;Delabie et al 1990;Aguiar-Passeti et al 1997;Arai et al 1999;Sunderkotter et al 2004;Kurata et al 2005;Terasaki et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…new pathway for pulmonary inflammation (35). The S100 protein family, especially S100A8 (29) and S100A9 (27), are cytoplasmic EF-hand Ca 2ϩ -binding proteins (36), which are some of the ligands that have been linked to human inflammatory and neoplastic diseases (37).…”
Section: Elevated Levels Of Metastasis In the Lungs Of Mice Lacking Umentioning
confidence: 99%
“…Knowledge of the expression and role of RAGE in host defense during pneumonia is limited. Morbini et al observed increased RAGE expression in patients with interstitial and postobstructive pneumonia [32]; this report left unanswered whether patients with bacterial pneumonia were included in the analysis. Notably, two other studies showed that constitutively present RAGE was not upregulated during pulmonary infl ammation associated with ALI or acute respiratory distress syndrome (ARDS): First, rats with ALI induced by intratracheally administered LPS displayed no change in the distribution of RAGEexpressing cells [29]; and second, patients with ARDS did not have increased pulmonary expression of RAGE [26].…”
Section: Rage Expression During Pneumoniamentioning
confidence: 92%
“…In particular, although the kidney is dramatically aff ected by microangiopathy and fi brosiswhich is substantially attributed to RAGE -in patients with diabetes, the lungs, with a signifi cantly higher baseline RAGE expression than the kidney, remain unaff ected. In addition, RAGE has been found to be specifi cally localized near the basal cell membrane within alveolar pneumocytes [32,35,36]. Th ese two observa tions raise the question as to whether RAGE has a function in normal healthy lungs.…”
Section: Rage During Pneumonia Localization and Role Of Rage In The Lmentioning
confidence: 97%
See 1 more Smart Citation